(untitled) (Journal of Parents and Teachers, 2023)
Nobody gives what does not have. This statement takes on special relevance in education. In this line, today, it is essential to talk about care and self-care. Knowing the keys to something so natural and inherent to the human being is simple. Realizing how and putting the person at the center will be the fundamental criteria and the great challenge we face.